2022
DOI: 10.1007/s40618-022-01777-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cardiometabolic risk profiles between Chinese and Finnish older adults with glucose impairment and central obesity

Abstract: Background Obesity and ethnicity play important roles in cardiovascular complications in patients with type 2 diabetes mellitus (T2DM). This study aimed to compare cardiometabolic risk profiles between Chinese and Finnish older adults of central obesity with prediabetes or T2DM. Methods Study subjects were 60–74 years old and originated from two population samples. The Finnish subjects came from the Kuopio Ischemic Heart Disease (KIHD) study (n = 1089), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The physical examination showed that the population was mostly healthy, with LDL levels within the normal range (< 120 mg/dL) [ 41 ]; hence this study cautiously speculates that the effect of LDL on islet function was insignificant. Moreover, previous studies have shown a significant association between LDL and diabetes in the Western population, whereas high TG levels were observed in the Chinese population [ 42 ]. In this study, the effect of obesity and high glucose level exceeded the effects of LDL and non-HDL on T2D risk in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The physical examination showed that the population was mostly healthy, with LDL levels within the normal range (< 120 mg/dL) [ 41 ]; hence this study cautiously speculates that the effect of LDL on islet function was insignificant. Moreover, previous studies have shown a significant association between LDL and diabetes in the Western population, whereas high TG levels were observed in the Chinese population [ 42 ]. In this study, the effect of obesity and high glucose level exceeded the effects of LDL and non-HDL on T2D risk in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Details of this study have been described previously. [18][19][20][21][22] Briefly, the SHiDS study was initiated in 2002 aiming to identify diabetes in subjects with known risk factors, that is, family history of diabetes, overweight or obesity, previously identified impaired fasting glucose or impaired glucose tolerance, history of gestational diabetes, polycystic ovary syndrome, hypertension, and dyslipidemia. Patients with previously diagnosed diabetes were not invited.…”
Section: Research Design and Methods Study Design And Subjectsmentioning
confidence: 99%